THE LEGAL RECONSTRUCTION OF STATE CIVIL APPARATUS (ASN) IN REGULATING ASN PERFORMANCE IN THE ERA OF GLOBALIZATION - Suud, Aghia Khumaesi (UNISSULA, 2022)
The era of globalization requires State Civil Apparatus (ASN) to understand information technology in carrying out public services. Until the discourse of Work From Anywhere (WFA) emerged as a form of changing the pattern of e-government performance to establish good governance. For this reason, a legal reconstruction of the ASN is needed so that it does not violate the merit system in the ASN Law. However, significant changes and training are needed in all respects to make this happen. By using normative juridical methods and secondary data, the author considers that it is necessary to analyze the reconstruction of ASN Law in regulating ASN performance in the Globalization Era and how the mechanism for changing digital-based performance patterns is. The result of this article is legal reconstruction is needed in ASN regulations and the discourse on implementing WFA for ASN can actually be carried out with a merit system mechanism that fulfills five performance indicators namely, productivity, service quality, responsiveness, responsibility and accountability well.